The reality of using Blended Learning in Arab Universities A case study on students of the University of Sharjah in the United Arab Emirates and students of the University of Hail in the Kingdom of Saudi Arabia: Analytical Comparative Study - Barhoumi, Wafa Omar (Al-Adab Journal, 2022)
This study aims to investigate the perceptions of students of College of Arts and Humanities and Social Studies regarding the importance and the utilization of blended learning at University Of Sharjah in United Arab Emirates and University of Hail at Kingdom of Saudi Arabia. This research also aims to determine how readily accessible the appropriate equipment and resources for implementing blended learning are, as well as what are the obstacles to implementing blended learning in the classroom. This study has adopted the descriptive approach. A questionnaire is administered to 200 students in each university. Data are analyzed quantitatively using the Statistical Package for Social Sciences (SPSS). Descriptive data including percentages and averages are presented. The results revealed that students from the University of Sharjah and the University of Hail agree on the importance of blended learning. However, both participants accept that it is still in use to some extent. Additionally, although students have a moderate level of agreement that the equipment and resources needed to incorporate blended learning are available, they have a low level of agreement on this issue. Furthermore, students believe that there are major obstacles to using blended learning in universities. The results show that there are gaps in the research sample's responses about the effectiveness of blended learning, the equipment needed to implement it, and the obstacles to applying it.Based on the findings of the study, the researcher recommends the following:1 - Developing of the current curriculum to meet the requirements of blended learning.This can be accomplished by forming a committee comprised of experts in the fields of education and computer science.2 - Providing and organizing training programs for teachers and students on the use of computers and the Internet.3 - Providing ongoing network technical support and maintenance.